The library computer lab transforms into a "thinking lab". Issue 1 (9th January 2017) - Massis, Bruce E.
Abstract : Purpose: The purpose of this column is to examine the process for the transition of library computer labs into "thinking labs", where existing library workstation space can be reallocated to provide more flexibility, freedom and creativity for the library patron. Design/methodology/approach: Literature review and commentary on this topic that has been addressed by professionals, researchers and practitioners. Findings: The transition of library computer labs into "thinking labs" is an initiative where library planners can experiment with ideas and concepts in library design to provide the most effective user experience through a "fresh perspective". Originality/value: The value in exploring this topic is to propose that library planners and designers create space unlike traditional designs to provide patrons with a more transformative thinking, learning and creative library experience.